Evolution of the south Pacific helium plume over the past three decades. (4th May 2017) - Lupton, J. E.; Jenkins, W. J.
Abstract: The recent GEOTRACES Eastern Pacific Zonal Transect in 2013 crossed the East Pacific Rise at 15°S following the same track as the 1987 Helios Expedition along the core of the mid‐depth helium plume that spreads westward from the East Pacific Rise (EPR) axis. The fact that several stations were co‐located with the earlier Helios stations has allowed a detailed comparison of the changes in the helium plume over the intervening 26 years. While the plume in many areas is unchanged, there is a marked decrease in plume intensity at longitude 120°W in the 2013 data which was not present in 1987. Recent radioisotope measurements along the plume track suggest that this decrease is due to the intrusion of a different water mass into the plume, rather than a modulation of hydrothermal input on the EPR axis. Analysis of GEOTRACES hydrographic data shows excess heat present in the plume up to 0.04°C, corresponding to a 3 He/heat ratio of ∼2.5 × 10 −18 mol J −1, similar to that found in mature hydrothermal vents. RAFOS floats deployed in 1987 indicate an average westward transport of ∼0.3 cm s −1 at 2500 m depth in the off‐axis plume, in agreement with recent estimates of ∼0.4 cm s −1 based on "aging" of the plume from 227 Ac/ 3 He ratios. Key Points: This paper explores changes in the south Pacific helium plume over the period of 1987–2013 Changes in the plume indicate changes in the mid‐depth circulation in the south east Pacific Analysis of RAFOS neutrally buoyant drifters from 1987 indicates westward transport at 0.3 cm/s in the plume core